10‐kHz Spinal Cord Stimulation for Chronic Postsurgical Pain: Results From a 12‐Month Prospective, Multicenter Study. Issue 8 (23rd July 2020) - Gupta, Mayank; Scowcroft, James; Kloster, Daniel; Guirguis, Maged; Carlson, Jonathan; McJunkin, Tory; Chaiban, Gassan; Israel, Atef; Subbaroyan, Jeyakumar
Abstract: Background: Chronic postsurgical pain (CPSP) can be caused by peripheral nerve injury (PNI) resulting from surgical procedures and has a significant neuropathic component. This prospective, single‐arm study was conducted to document the effectiveness of 10‐kHz spinal cord stimulation (10‐kHz SCS) as a treatment for patients with CPSP. Methods: Subjects with CPSP who were refractory to conventional medical interventions and reported pain scores of ≥5 cm on a 10‐cm VAS underwent trial stimulations lasting up to 14 days. Epidural leads were implanted at locations appropriate for the primary area of pain, and trials resulting in ≥40% pain relief were considered successful. Subjects with successful trials underwent implantation with a permanent 10‐kHz SCS system and were followed for 12 months after implantation. Results: Of the 34 subjects who underwent trial stimulation, 1 was withdrawn early and 29 (87.9%) had a successful trial and received a permanent implant. After 12 months of treatment, the mean VAS score decreased by 6.5 cm, the response rate was 88.0% (22/25), and 18 subjects (62.1%) were remitters with VAS scores sustained at ≤3.0 cm. Scores for all components of the short‐form McGill Pain Questionnaire 2 were significantly reduced, including affective descriptors of pain. Pain catastrophizing and vigilance, patient function, physical and mental well‐being, and sleep quality all improved over the course of the study. No neurologic deficits reported in the study. Conclusions: 10‐kHz SCS is effective and tolerated in patients with CPSP, and further study of its clinical application in this population is warranted.